Individual differences in the acquisition of restricted collocations - Abd Halim, Hasliza; Kuiper, Koenraad (2018)
The acquisition of verb-noun collocations (e.g. make a mistake) causes great difficulties to (adult) L2 learners for several reasons (Boers, Demecheleer, Coxhead and Webb, 2014). Thus, investigating the use of collocation in English language learning is important as such study may inform us on the use of restricted collocations in English language teaching and learning including in the Malaysian context. Apart from the difficulties in the acquisition of collocations, Dornyei and Skehan (2003), and Sawyer and Ranta (2001), have found that individual difference factors have significant impacts on language learning in general. Apart from that, Schmitt, Dornyei, Adolphs & Durow (2004) argue that these individual differences might also influence the acquisition of formulaic language. The results of this study provide support for the above finding. Individual differences are indeed a factor. A new testing approach is proposed; the semantic plausibility metric, which is used as a tool for this study, and is shown to be useful as a measure of vocabulary acquisition as well as for looking at learners’ test taking strategies (Halim, 2014). This study also suggests that malformed collocational choices should be viewed positively.